GSCM: practices, trends and prospects in Indian context - Soda, SHEETAL; Sachdeva, Anish; Garg, Rajiv Kumar (Journal of manufacturing technology management, 2015)
Purpose – Environmental friendliness, in context of industrial operations, is an issue that has evoked much interest among environmentalists, governments, academicians and other sections of society in recent times. The said development has been more profound and broad-based in developed economies of the world, though, the trend is catching fast in developing countries, as well. Green Supply Chain Management (GSCM) is a management technique that aims to make a supply chain eco-friendly, without diluting the organizational objectives. The purpose of this paper is to investigate the scale of adoption and implementation of GSCM practices in the context of Indian industries. Design/methodology/approach – The investigation used literature review approach to determine the current status of implementation of GSCM by Indian industry, and associated aspects of the same. Literature pertaining to the subject in context of non-Indian industries has also been studied for the purpose of rudimentary knowledge on the management concept, as well for comparing the measures taken by foreign-based companies with Indian ones. Findings – The study shows that in general, Indian companies are lacking on the front of adoption and implementation of GSCM measures in their supply chains. Though, certain companies are showing appreciable enthusiasm for the eco-friendly concept, the same does not apply to majority of the Indian enterprises, owing to a multitude of factors. GSCM has the potential to drive economic gains, and can act as a big motivator for companies to go green. As India leaps towards higher levels of industrialization and economic growth, GSCM becomes more of a necessity rather than an option for Indian companies to survive the competition. Practical implications – Findings from this study helps in discerning the present status of GSCM in the country, and assess the same in comparison to that of developed countries. The findings will also help the firms to have a greater understanding of their current standing and the possible gains that can accrue by adoption of GSCM practices in real. The philosophy, stance and endeavours of government with respect to GSCM has also been spelt out in the paper. The paper contributes to the literature by providing empirical evidence on various aspects of GSCM in the country and the trajectory that it will chart in future. Originality/value – The paper though, brings forth the findings of other researches on the subject of GSCM practices in India in a consolidated manner, yet its value is reflected in the cohesive manner in which contrary findings have been analysed to present a comprehensive and holistic picture of GSCM implementation in India. An attempt has been made not only to assess the inputs of individual firms, but also of government and other stakeholders in their efforts to make supply chains more environment friendly.